PENGARUH NILAI PASAR, LEVERAGE DAN PROFITABILITAS TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR PADA INDEKS LQ 45 - Maulida Silvani, - (2019)
This study was conducted to examine the effect of market value, leverage, and profitability to stock return on company that listed on index LQ45. Thepopulation in this research were 54 company that listed on index LQ45 period 2015to 2017. The sample obtained in this study amounted to 26 company selected bypurposive sampling method. Total observation data obtained in this study are 78data period 2015 to 2017. Data analysis is done using the Microsoft Excel 2016and hypothesis testing in this study using a Panel Data Regression Analysis with the program E-Views 9.0 and the level of significance of 5%. The results of the test were obtained (1) Market Value is represented by EPS effect significantly to StockReturn, (2) Leverage is represented by DER no effect significantly to Stock Return, (3) Profitability is represented by ROE no effect significantly to Stock Return.